Investigating the Role of Winged Shear Walls and Their Behavior in the Aftershocks Applied to the Structure and Behavior of the Joints (Case Study: Mashhad Suburbs Meat House Buildings) - Siapoush, Abdolhossein; Mahmoodzadeh, Amir (International Journal of Engineering and Technology, 2018)
Since Iran is one of the most earthquake-prone areas in the world, attention to earthquakes should be one of the main goals of construction experts. In Iran, as a result of the synchronization of sciences such as seismology, structural engineering, geotechnical engineering with the aim of improving the performance of structures against earthquakes and, as a result of increasing their durability and safety, the building design regulations for earthquakes (standard 2800), is presented. Case The review in this article is that the occurrence of severe aftershocks can cause further damage or sometimes collapse and damage to structures that have not been damaged by major earthquakes. Therefore, calculating the probability of increasing vulnerability in important structures such as service structures after the occurrence of the major earthquake, such as hospitals and firefighting centers, and crisis management (especially in Iran, which is an earthquake country), and the importance of studying the behavior of aftershocks is absolutely necessary. In this research, the role of winged shear walls and their behavior in the post-seismic to the structure and then the behavior of the joints have been investigated. Mashhad suburbs, which are of concrete structures, are evaluated for aftershock vulnerability using soft Specialist Etabs and 22SPSS. The results show that, with increasing classes, the maximum amount of shear force distribution in the walls increase. The increase in the wing reduces the horizontal position of the wall. By increasing the length of the wall's wings, the depth decreases. By increasing the height of the structure, walls with 2 meter wings have been able to show relatively good behavior and reduce seismic effects on the structure. In high strength concrete, the effect of high resistance cement consumption on cement consumption has been higher and in connection with 20 hardening tensile joints occurred in bonding behavior. In the connection with the 16th joints, the least increase in hardening and displacement occurred, and the increase in the concrete category caused an increase in damping.Â Â